Study on Thickness Thinning Ratio of the Forming Parts in Single Point Incremental Forming Process - Mingshun Yang; Zimeng Yao; Yan Li; Pengyang Li; Fengkui Cui; Lang Bai (Advances in Materials Science and Engineering, 2018)
An excessive thickness-reducing ratio of the deformation zone in single point incremental forming of the metal sheet process has an important influence on the forming limit. Prediction of the deformation zone thickness is an important approach to control the thinning ratio. Taking the 1060 aluminum as the research object, the principle of thickness deformation in the single point incremental forming process was analyzed; the finite element model was established using ABAQUS. A formula with high accuracy to predict the deformation zone thickness was fitted with the simulation results, and the influences of process parameters, such as tool diameter, step down, feeding speed, sheet thickness, and forming angle, on thinning ratio were analyzed. The accuracy of the finite element simulation was verified by experiment. A method to control the thinning rate by changing the forming trajectory was proposed. The results showed that the obtained value by using the fitted formula is closer to the experimental results than that obtained by the sine theorem. The thinning rate of the deformation zone increases with the increase of tool diameter, forming angle, and sheet thickness and decreases with the increase of step down, while the feeding speed had no significant effect on the thinning ratio. The most important factor of the thinning ratio is the forming angle, and the thinning ratio can be effectively reduced by using the forming trajectory with a uniformly distributed pressing point.